It's all in Marshall: the impact of external economies on regional dynamics - David B. Audretsch; Oliver Falck; Stephan Heblich (Center for Economic Studies and ifo Institute (CESifo), 2007)
Marshall's student Pigou noted: It's all in Marshall. From a static point of view, this seems rather bold in a constantly changing world. However, this statement becomes more plausible in a dynamic context, where principles are subject to change. Indeed, over time, Marshall's concept of external economies gained fresh perspective as new concepts of regional characteristics and agglomeration evolved. This paper focuses on the impact of region and industry on dynamics and growth, distinguishing between industrial districts, industrial agglomerations and urban agglomerations. Based on these three types, we use a comprehensive large dataset on German regions to test the following: (1) these regions can be characterized by given location variables describing geographic location, firm structure, and surrounding location factors and (2) every region's locational variables affects its potential for dynamics.
Keywords: O18; R11; R12; 330; Regionale Entwicklung; Agglomerationseffekt; Urbanisierungseffekt; Industriegebiet; Standortfaktor; Theorie; Deutschland